Health and Hygiene in the light of Qu‘ran and Sunnah - Sheikh, Dr Riyaz Ahmad (European Journal of Life Safety and Stability (2660-9630), 2022)
“He who has health, has hope; and he who has hope, has everything” After faith, health in (Islam) is considered as one of the greatest sanctifications given to humankind by Allah (S.W.T) there are number of reference in Quran and Sunnah of Prophet Muhammad (S.A.W) regarding the significance and implication of this blessing. The Holy Quran expresses the most general instructions about nutrition and health of humankind, in chapter 80 verse 24 (Surah Abase, Ayat 24) Allah (S.W.T) states: “Of course man must be careful of food and nutrition”. And in chapter 2 verse 172 (Surah Baqarah, Ayat 172) “People of faith, if you are worshipper, eat from healthy food that we have given to you and give thanks to God, if you are worshiper.” The Prophet (S.A.W) said, ‘there are two blessings which many people do not appreciate: health and leisure’. He (S.A.W) also said, “No blessing other than faith is better than well-being.” It is religious obligation; therefore, to safeguard this blessing and not mishandle it through ill practice, for that there is being severe punishment, according to Allah’s immutable laws. The preservation of this blessing can only be achieved through different ways, means and mechanism, hygiene is one of them. This is the fact that there is positive co-relation between health and hygiene; rather we can say good health depends on good hygiene. Hygiene is one the measures to preserve and enhance good health. From Islamic perspective, good health is vital for properly performing the different Islamic duties including salah (offering five times daily’s prayer), taking Ramadan’s fasts and Hajj. The present study is an attempt to deliberate on the dependency of health on hygiene in light of basic sources of Islam (Quran and Sunnah of Prophet Muhammad s.a.w)